When daughters bake a heaven / Amirul Hakim Zulkifli, Hasiful Fata Talhah and Nor Hafizah Mazlan - Zulkifli, Amirul Hakim; Talhah, Hasiful Fata; Mazlan, Nor Hafizah (Faculty of Hotel & Tourism Management, UiTM Pulau Pinang, 2023)
Be prepared to embark on a dessert journey like no other! The Daughters Bake Cafe has redefined the art of indulgence, elevating desserts to a level of sophistication and creativity that is simply unparalleled. From the moment you step inside this enchanting oasis of flavors, you will find yourself captivated by the elegant ambience and the alluring aroma of freshly baked treats. The decor exudes an opulent charm, combining soft pastel hues with plush seating and a chandelier that casts a warm glow over the space. The attention to detail in every aspect of the cafe's design reflects the level of dedication and passion the owners have poured into creating this haven for dessert connoisseurs. Now, let's delve into the star of the show - the desserts themselves Each item on the menu is a masterpiece, skilfully crafted by a talented team of pastry chefs. More surprisingly, the chef is also the owner of the cafe, a former student who is from the first batch Diploma in Pastry Art, Universiti Teknologi MARA Pulau Pinang. She uses only the finest and freshest ingredients. The very friendly Chef offered expert recommendations, and I settled on three delectable creations to savour. First on the list was "The Godiva". The texture of this chocolate cheesecake was flawless. The velvety smoothness of the cheesecake filling combined with the slightly denser but still creamy milk chocolate Cremieux and roasted hazelnut on top made each bite an unforgettable experience. The crust was firm enough to hold its shape yet crumbled effortlessly, adding a delightful crunch to each heavenly mouthful.